2021
DOI: 10.1108/ijmpb-05-2020-0154
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the readiness of a megaproject

Abstract: PurposeA vast proportion of global megaprojects have not performed up to the expectations of their stakeholders. A failed megaproject has the potential even to derail the economy of a country where it was implemented. Stakeholders must, therefore, ensure that they do not invest in megaprojects that are bound to fail. But, how can stakeholders consistently identify such megaprojects? This paper develops a framework for a metric that can help stakeholders measure the readiness of a megaproject.Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Megaprojects, with their huge spatial and temporal characteristics have been significant drivers and boosters of economic and social development [ 1 ]. Thus, both public and private organizations worldwide have resorted to the development of megaprojects as one of the most preferential routes to provide benefits to local municipalities and society at large [ 2 ]. However, they are typically characterized by “enormous resource consumptions and significant environmental impacts” [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Megaprojects, with their huge spatial and temporal characteristics have been significant drivers and boosters of economic and social development [ 1 ]. Thus, both public and private organizations worldwide have resorted to the development of megaprojects as one of the most preferential routes to provide benefits to local municipalities and society at large [ 2 ]. However, they are typically characterized by “enormous resource consumptions and significant environmental impacts” [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Megaproject leaders lacking required leadership competencies may fail to support the containment of high complexity and deep uncertainty. Leadership in megaprojects is dynamically transferred between related actors and thus cannot be attributed to one person; therefore, leadership and commitment from key project actors are crucial to successful project delivery (Cao et al, 2021;Shenoy and Mahanty, 2021).…”
Section: Irresponsible and Unqualified Key Participantsmentioning
confidence: 99%
“…Moreover, authoritarianism-dominant paternalistic leadership is considered to contribute to the remarkable achievements in megaproject delivery in China (Wan et al, 2020). Senior executives have substantial authority and power and the voices of team members are restrained, which inhibits stakeholder engagement and reduces transparency in decision-making (Shenoy and Mahanty, 2021). When regulatory mechanisms are ineffective in exposing project misbehavior, asymmetric power relationships in paternalistic leadership will lead to greater information opaqueness and opportunistic decision making.…”
Section: Information Uncertainty and Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…It can avoid the impalpable and arbitrary result. Therefore, the analysis showed that the identified papers could be categorized into five clusters: megaproject management in general [29,[116][117][118][119], megaproject sustainability [27,34,[120][121][122][123], megaproject governance [22,[124][125][126][127][128][129], megaproject investment and finance [44,48,92,[130][131][132], and megaproject risk management [95,112,[133][134][135][136]. When the topic of a paper was related to multiple clusters, the paper was classified into the most closely related cluster.…”
Section: Research Topics Of the Identified Papers In Megaproject Management Researchmentioning
confidence: 99%